Investigating the effect of ZIF-8@PEI filler and its comparison with ZIF-8 in mixed matrix membranes for CO2/CH4 separation with the help of DFT study - Ajay V. Gawali; Sapna Gawali; Surendra Sasikumar Jampa; Manish Kumar Sinha (Sustainable Chemistry for Climate Action)
In this study, Zeolitic Imidazolate Framework-8 (ZIF-8) and modified ZIF-8 (ZIF-8@PEI)with polyethyleneimine (PEI) were used as dispersed particles inside the polysulfone (PSF) matrix to separate CO2 and CH4. The distributions of dispersed particles in mixed matrix membranes (MMMs) were analysed with the help of Fourier transfer infrared radiation, Thermal gravimetric analysis, Scanning electronic microscope and X-ray diffraction. The mixed matrix membranes investigated the permeability and selectivity of pure gas (CO2) and mixed gas (CO2/CH4). It was highest at 5 wt% ZIF-8@PEI blended into the PSF matrix. In case of pure gas studies, we investigated the CO2 permeability (18.10 Barrer) and CO2/CH4 selectivity (23.91) as compared to ZIF-8/PSF MMM (10.36 Barrer, 5.81); and in case of mixed gas studies, the CO2 permeability (17.11 Barrer) and CO2/CH4selectivity (21.28) as compared to ZIF-8/PSF MMM (7.86 Barrer, 4.21).Using DFT studies, the interaction energies of the ZIF-8@PEI material with CO2 and CH4 gas molecules werefound to be -74.39 kJ/mol and -23.25 kJ/mol, respectively. It was more toward the ZIF-8@PEI-CO2geometry complex.From the observation, the experimentalgas permeation results and DFT studiesinvestigated that ZIF-8@PEI filler can be a good candidate for applying CO2 capture.